Variations in olfactory function among bipolar disorder patients with different episodes and subtypes - Li, Chunyang; Hong, Liu; Zou, Laiquan; Zhu, Yiping; Ye, Jianfu; Wu, Fenlan; Chen, Chao (Frontiers in Psychiatry, 2023)
Purpose Most studies on olfactory function in individuals with bipolar disorder (BD) have not distinguished between the different subtypes or between the acute phase (mania or depression) and euthymic state. In this study, we compared olfactory function among BD patients with different subtypes and episodes to explore the potential use of olfactory function as a biomarker for the early identification of BD. Patients and methods The study sample consisted of 117 BD patients who were hospitalized between April 2019 and June 2019, and 47 healthy volunteers as controls. The BD patients were divided into a bipolar I disorder (BD I) (n = 86) and bipolar II disorder (BD II) group (n = 31) according to the different subtypes, and divided into depressive BD (n = 36), manic BD (n = 44), or euthymic BD (n = 37) groups according to the types of episodes they experienced. We assessed olfactory sensitivity (OS) and olfactory identification (OI) via the Sniffin’ Sticks test and used the Hamilton Depression Rating Scale (HAMD) and Young Manic Rating Scale (YMRS) to evaluate BD characteristics among all subjects. Results Compared with controls, the participants with BD showed decreased OS and OI. We found statistically significant differences in OS and OI between the BD I group and controls, as well as differences in OS between the BD I and BD II group. Least-significant difference multiple comparisons revealed statistically significant differences in OS between the depressive BD group, manic BD group and controls and also between the manic BD and euthymic BD group. OI was positively correlated with the YMRS score in the BD I group and OS was negatively correlated with the HAMD score in the BD II group. Conclusion This may be the first study to compare olfactory function in patients with BD I vs. BD II via pairwise comparisons. Our findings suggest that OS may have potential as a biomarker for distinguishing the different subtypes of BD and as a state-related biomarker for differentiating the acute phase from the euthymic state of BD. However, further prospective research is warranted.